Dielectric permittivity calculation of composites based on electrospun barium titanate fibers. (8th April 2015) - Ávila, H A; Reboredo, M M; Parra, R; Castro, M S
Abstract: On the basis of theoretical predictions and experimental results, an empirical method using upper bound equation of the rule of mixtures (ROM) is reported to predict the dielectric permittivity of barium titanate nanofibers. In addition, composites with low volume fraction of BaTiO3 fiber layers embedded in epoxy resin were prepared and characterized. The relative permittivities of composites with perpendicular and parallel configurations, with respect to the electrodes, were calculated by means of the ROM model. The predicted permittivities matched precisely the obtained experimental values.